1995
DOI: 10.1111/j.1748-1716.1995.tb09916.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxin of the marine alga Prymnesium patelliferum enhances voltage dependent Ca2+‐currents, elevates the cytosolic Ca2+‐concentration and facilitates hormone release in clonal rat pituitary cells

Abstract: The marine flagellate Prymnesium patelliferum produces toxins lethal to fish. The toxin extracted from the alga has haemolytic, cytotoxic and neurotoxic effects, but the action mechanisms of the toxin are not known in detail. We have examined the toxin effects on the voltage sensitive Ca(2+)-currents, the cytosolic Ca(2+)-level ([Ca2+]i) and the prolactin release in clonal rat anterior pituitary GH4C1 cells, which possess T- and L-type Ca(2+)-channels. The trans-membrane Ca(2+)-current was recorded using whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They also showed that the toxin increases the Ca 2+ and Na + influx, through the plasma membrane of synaptosomes. It is also reported that prymnesium toxin induces Ca 2+ influx in other cell preparations, such as rat pituary and glioma cells (Kolderup et al, 1995;Igarashi et al, 1998). These findings indicate that one could expect to find toxin-induced release of neurotransmitters.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…They also showed that the toxin increases the Ca 2+ and Na + influx, through the plasma membrane of synaptosomes. It is also reported that prymnesium toxin induces Ca 2+ influx in other cell preparations, such as rat pituary and glioma cells (Kolderup et al, 1995;Igarashi et al, 1998). These findings indicate that one could expect to find toxin-induced release of neurotransmitters.…”
Section: Discussionmentioning
confidence: 86%
“…This was attributed to an effect on the Na + gradient, diminishing the driving force for uptake. Later it was shown that the algal extract of prymnesium also could induce influx of Ca 2+ into both synaptosomes and rat pituitary cells (Kolderup et al, 1995;Mehldal et al, 1994). These findings indicate that the inhibitory effect of the toxin on glutamate uptake also may be a result of spontaneous release of neurotransmitters.…”
mentioning
confidence: 97%